HUMAN RESOURCE MANAGEMENT PRACTICES IN AUTOMOBILE INDUSTRY – A STUDY - S. SHASHILA; RANI, S. VENNILA FATHIMA (International Journal of Psychosocial Rehabilitation, 2020)
The organization enjoys a vital situation in commercial center with his esteemed clients who are incredibly happy with the worldwide norm and brand. Enjoying 98% customer maintenance, Harley fundamentally keeps the workforces who are the dear loved ones of his representatives. Significantly subsequent to having such a wonderful achievement it confronted difficulties for example rivalry from lower estimated contenders and venture into abroad markets. This investigation intends to explain the job of HR in getting changes the association. Data is gathered by optional information. The discoveries uncover the work done, giving a chance to measure the organization with other world-class organizations and distinguish the handy activities takes to improve our HR capacity and set the stage for future activities. Yet in addition receiving the moderate work framework and human asset formative polices. The human asset advancement concerning deals group of Indian vehicle industry during Globalization is talked about in this paper. HR review is a beneficial measure that can spare the organization time and cost.